2019
DOI: 10.15376/biores.15.1.1074-1084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the manufacturing conditions on the VOCs emissions of particleboard

Abstract: The volatile organic compounds (VOCs) emitted from wood-based panels are hazardous to indoor air quality. Usually, the VOCs are derived from the adhesive, chemical compounds, and wood components. However, there has been little research focusing on the effects of manufacture conditions on the VOC emissions. In this study, the effects of density, thickness, and resin content on total VOC (TVOC) and individual VOCs were investigated by the small chamber method and gas chromatography and mass spectrometry (GC/MS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In this study the barrier effect of melamine-impregnated paper of 120 g/m 2 was found to be better than that of melamine-impregnated paper of 80 g/m 2 [29]. Sun et al (2020) analyzed the effect of the manufacturing conditions on the VOCs emitted from coated particleboard samples using a GC/MS (Trace DSQ II, Thermo Scientific, Waltham, MA, USA) system consisting of a trace gas chromatographic and a DSQ • C mass selective detector [30]. Ho et al (2011) evaluated the emission rates of volatile organic compounds released from newly produced furniture products using a large-scale chamber testing method.…”
mentioning
confidence: 99%
“…In this study the barrier effect of melamine-impregnated paper of 120 g/m 2 was found to be better than that of melamine-impregnated paper of 80 g/m 2 [29]. Sun et al (2020) analyzed the effect of the manufacturing conditions on the VOCs emitted from coated particleboard samples using a GC/MS (Trace DSQ II, Thermo Scientific, Waltham, MA, USA) system consisting of a trace gas chromatographic and a DSQ • C mass selective detector [30]. Ho et al (2011) evaluated the emission rates of volatile organic compounds released from newly produced furniture products using a large-scale chamber testing method.…”
mentioning
confidence: 99%
“…The "planks" are cut and put together into a range of interior products, e.g., wall tiles, yoga blocks, and coasters (Fig. 6a) (Sun et al 2019). They also produce tabletops made from chopsticks.…”
Section: Recycling Strategies Of Waste Chopsticksmentioning
confidence: 99%
“…There has been some research on the effects of the hot-pressing condition, adhesive, heat treatment, and secondary processing of panels on VOCs and formaldehyde emissions of particleboards. In those reports it has been shown that the hot-pressing temperature, time, resin, and density affect the pollutants (Lee and Kim 2012;Liu et al 2012;Candan and Akbulut 2013;Sun et al 2020). Furthermore, the drying and hot-pressing techniques were helpful in reducing the formaldehyde and VOCs emission from wood-based panels (He et al 2012).…”
Section: Introductionmentioning
confidence: 99%